High specific energy ternary nanocmposite polyaniline:Manganeese dioxide@ MWCNT electrode for asymmetric supercapacitor. (June 2020) - Grover, Sonia; Sahu, Vikrant; Singh, Gurmeet; Sharma, Raj Kishore
Highlights: A co-axial system of polyaniline and MnO2 was generated over functionalized MWCNT. An asymmetric supercapacitor device is fabricated which can be cycled in wide voltage window of 2 V. Due to synergism, electrochemical performance is enhanced. Abstract: A layer of highly dispersed manganese oxide (MnO2 ) nanoparticles in polyaniline (PANI) was deposited over functionalized MWCNT using insitu chemical polymerization. Obtained Coaxial MWCNT/PANI:MnO2 ternary nanocomposite was used as positive electrode with MWCNT negative electrode in an asymmetric supercapacitor (ASC) device. The proposed design utilizes the pseudo capacitive charge in a different potential range of the ASC device. Microstructural investigations confirmed the wrapping of MWCNT by a layer of MnO2 dispersed PANI. This leads to highly porous and homogeneous morphology of the ternary nanocomposite. Due to synergism between PANI and MnO2 nanoparticles over MWCNT, the electrical properties of the ternary nanocomposite are significantly improved. It is observed that the proposed ASC device can be cycled up to a cell voltage 2.0 V reversibly. The above combination of materials in ASC device exhibited very high specific energy 190 Wh/kg and specific power at 1 mA/cm 2 . This device demonstrated better rate capability by maintaining 78% specific capacitance after continuously 2000 charge discharge cycles. Graphical abstract: Image, graphical abstract